Utility of fractional excretions of electrolytes (FEX) as biomarkers in kidney diseases. - Castro-Flores, A.; Christopher Barbier, O.; González-Galarza, F.F.; Delgadillo-Guzmán, D. (Revista de Ciencias Médicas Torreón, 2025)
Introduction. The evaluation of electrolyte concentrations has been of interest for the diagnosis and management of kidney diseases and disorders. These concentrations could provide a more complete picture that allows establishing multiple therapeutic options and, therefore, a better prognosis for patients. Fractional excretion of electrolytes (FEX) reflects the capacity for excretion of these solutes corresponding to the urinary excretion of creatinine and has been used to diagnose electrolyte imbalances and differentiate kidney diseases. Previous studies have identified that increased fractional electrolyte excretions may be a sign of a decrease in glomerular filtration rate, even before an elevation in serum creatinine.Objective: To review the usefulness of fractional excretions of sodium (Na+), potassium (K+) and magnesium (Mg+) as biomarkers in kidney pathologies.Methodology: A search and review of the literature was carried out regarding fractional excretion of sodium (FENa), fractional excretion of potassium (FEK) and fractional excretion of magnesium (FEMg) as biomarkers in kidney pathologies.Results: According to the consensus of the literature, FENa seems to have a more important role in acute kidney injury to differentiate the prerenal or renal origin of this pathology. In addition, FEMg could be useful to evaluate the progression of chronic kidney disease and identify tubular damage. Regarding FEK, there is currently little evidence on its usefulness as a biomarker in kidney pathologies.Conclusion: To interpret FEX in the renal context, it is suggested to perform an individual approach rather than through a general approach.
Keywords: fractional excretion of magnesium; fractional excretion of sodium; fractional excretion of potassium; kidney pathologies